Interatomic resonant Auger effect in N2O. (22nd October 2020) - Deinert, Sascha; Schrodt, Alexander; Hartmann, Gregor; Achner, Alexander; Artemyev, Anton N; Ehresmann, Arno; Hans, Andreas; Ilchen, Markus; Glaser, Leif; Scholz, Frank; Seltmann, Jörn; Viefhaus, Jens; et al.
Abstract: The interatomic resonant Auger effect in N2 O is investigated experimentally and theoretically. We observe variations of the ratio between the yields of 1 s -photoionization of the central and terminal nitrogen atom in the photon energy range across the O 1 s → π * excitation. The present ab initio calculations of electronic structure and dynamics attribute these variations to the Fano interference between the direct N 1 s -photoionizations and the resonant O 1 s → π * excitation followed by Auger decays into the respective core–shell continua. The theory reveals that this interatomic core–hole-transfer effect is governed entirely by an energy transfer mechanism, and not by charge transfer.